2016
DOI: 10.4012/dmj.2015-132
|View full text |Cite
|
Sign up to set email alerts
|

Application of neutral electrolyzed water to disinfection of alginate impression

Abstract: Neutral electrolyzed water was developed with new concepts of long-term good durability and minimum corrosiveness to metal in addition to its excellent bactericidal activities similar to acid type of electrolyzed waters. The present study examined the bactericidal effects of the neutral electrolyzed water on disinfection of the alginate impression of a dental arch model contaminated by bacteria. Only 1-min immersion in neutral electrolyzed water could sufficiently disinfect the alginate impression including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
(22 reference statements)
1
16
0
1
Order By: Relevance
“…The bactericidal effect of AW (pH = 2.4) has been verified to deteriorate rapidly but the pH still kept its acidity in three month storage period, while the acidity (pH = 6.9) and bactericidal activity of NW remains stable over the same period 33 . AW has been reported to exert a demineralization effect on enamel, raising concern over its effects on teeth when used as a mouthwash 28 . This study was focused on evaluating the influence of different pH values of EW on the microhardness of dentin at various depths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bactericidal effect of AW (pH = 2.4) has been verified to deteriorate rapidly but the pH still kept its acidity in three month storage period, while the acidity (pH = 6.9) and bactericidal activity of NW remains stable over the same period 33 . AW has been reported to exert a demineralization effect on enamel, raising concern over its effects on teeth when used as a mouthwash 28 . This study was focused on evaluating the influence of different pH values of EW on the microhardness of dentin at various depths.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the pH of AW is below the critical pH for demineralization of enamel (pH = 5.2) and dentin (pH = 6.7) 35 . It has been reported to etch enamel in a manner similar to that of phosphoric acid 28 . AW has been reported to maintain its low pH even though the bactericidal effect decreased 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,10 Zaleca się, by opłukanie wycisku wodą, a następnie jego właściwa dezynfekcja miały miejsce możliwie jak najszybciej po zakończonej procedurze pobierania wycisku. 20,23…”
Section: Conclusion Due To the Increased Epidemic Regime The Develounclassified
“…Regarding several electrolyzed waters containing mainly HOCl, we reported their storage stability 21) , corrosion behaviors 22) , and their ability to remove bacteria from root canals 19) , dental instruments 23) , and prostheses 24) . Based on our results, neutral electrolyzed water (NW) might be the electrolyzed water that is most acceptable for clinical use because of its high storage stability 21) and lower corrosive effect on metals 22) , showing equivalent bactericidal activity 21,24,25) while disinfecting denture bases 24) , impressions [25][26][27] , and impression trays 27) . In our previous study, we reported that strongly acidic electrolyzed water showed marked decalcification, and the weakly acidic type showed slight decalcification following a 1-week immersion, whereas the neutral type showed no harmful effects on human enamel 28) .…”
Section: Introductionmentioning
confidence: 99%